Answer:
B
Step-by-step explanation:
![E=\dfrac{1}{2}mv^{2}\\\\\\2E = mv^{2}\\\\\dfrac{2E}{m}=v^{2}\\\\\\\sqrt{\dfrac{2E}{m}}=v](https://tex.z-dn.net/?f=E%3D%5Cdfrac%7B1%7D%7B2%7Dmv%5E%7B2%7D%5C%5C%5C%5C%5C%5C2E%20%3D%20mv%5E%7B2%7D%5C%5C%5C%5C%5Cdfrac%7B2E%7D%7Bm%7D%3Dv%5E%7B2%7D%5C%5C%5C%5C%5C%5C%5Csqrt%7B%5Cdfrac%7B2E%7D%7Bm%7D%7D%3Dv)
Answer:
![P(0.26 \leq p \leq 0.43)=0.7204-0.0032=0.7172](https://tex.z-dn.net/?f=P%280.26%20%5Cleq%20p%20%5Cleq%200.43%29%3D0.7204-0.0032%3D0.7172)
Step-by-step explanation:
Normal distribution, is a "probability distribution that is symmetric about the mean, showing that data near the mean are more frequent in occurrence than data far from the mean".
The Z-score is "a numerical measurement used in statistics of a value's relationship to the mean (average) of a group of values, measured in terms of standard deviations from the mean".
The population proportion have the following distribution
And we can solve the problem using the z score on this case given by:
![z=\frac{p_o -p}{\sqrt{\frac{p(1-p)}{n}}}](https://tex.z-dn.net/?f=z%3D%5Cfrac%7Bp_o%20-p%7D%7B%5Csqrt%7B%5Cfrac%7Bp%281-p%29%7D%7Bn%7D%7D%7D)
We are interested on this probability:
![P(0.26 \leq p \leq 0.43)](https://tex.z-dn.net/?f=P%280.26%20%5Cleq%20p%20%5Cleq%200.43%29)
And we can use the z score formula, and we got this:
![P(\frac{0.26 -0.4}{\sqrt{\frac{0.4(1-0.4)}{91}}} \leq Z \leq \frac{0.43 -0.4}{\sqrt{\frac{0.4(1-0.4)}{91}}})](https://tex.z-dn.net/?f=P%28%5Cfrac%7B0.26%20-0.4%7D%7B%5Csqrt%7B%5Cfrac%7B0.4%281-0.4%29%7D%7B91%7D%7D%7D%20%5Cleq%20Z%20%5Cleq%20%5Cfrac%7B0.43%20-0.4%7D%7B%5Csqrt%7B%5Cfrac%7B0.4%281-0.4%29%7D%7B91%7D%7D%7D%29)
![P(-2.726 \leq Z \leq 0.584)](https://tex.z-dn.net/?f=P%28-2.726%20%5Cleq%20Z%20%5Cleq%200.584%29)
And we can find this probability like this:
![P(-2.726 \leq Z \leq 0.584)=P(Z](https://tex.z-dn.net/?f=P%28-2.726%20%5Cleq%20Z%20%5Cleq%200.584%29%3DP%28Z%3C0.584%29-P%28Z%3C-2.726%29%3D0.7204-0.0032%3D0.7172)
Answer:
subtraction property
Step-by-step explanation:
because you subtracted 12x from 16x to get 4x+5=-6
20x4=80
i am assuming this is correct this is how i learned just take all numbers in equation and multiply by each other
Answer:
g(x) = 2(x - 2)^2 + 2 plot (see attachment)
Step-by-step explanation: